Análise da resistência ao cisalhamento de concreto reforçado com macro fibras de polietileno por meio do ensaio de push-off - Silva, Isabela Ereno da (2024)
Fibers are employed as structural reinforcement in concrete, due to their ability to transfer stress through cracks. Flexural, impact, fatigue resistance, and toughness and ductility improvement are examples of fiber influence on concrete mixtures. For fiberreinforced concrete designs, designers usually adopt shear strength values obtained through bending test results. However, a structure subjected to pure shear forces tends to fail at geometric discontinuity locations without flexural behavior. Therefore, a better understanding of fiber-reinforced concrete behavior under shear forces is necessary. For such analysis, one of the commonly adopted tests is the push-off test, in which specimens are in Z-shaped form. Its main advantages include the reduction of sample dimensions and the possibility of using mechanical presses, providing greater accessibility for test execution, and enabling studies with extensive sample groups. This research studied the direct shear strength of synthetic macro fiber-reinforced concrete, through push-off tests. The effect of fiber addition to the concrete mix was evaluated through workability, compressive strength, and flexural tensile strength. Behavior between mixtures with and without fibers, as well as the addition of different fiber proportions to the mixture, was compared. The possibility of minimum shear reinforcement replacement by synthetic macro fiber and the possibility of using literature and standard equations to estimate the shear strength of fiber-reinforced concrete (FRC) were also investigated. The research comprised mixtures with fiber addition of 0 kg/m3, 4.85 kg/m3, and 14.55 kg/m3. Compressive strength, toughness, and direct-shear tests (push-off) were conducted. It was observed that the fibers significantly reduced the workability of concrete. The addition of 0.5% and 1.5% fibers reduced the compressive strength by 19.62% and 29.58%, respectively. Fiber addition did not influence significatively the tensile strength in flexion. Despite the negative impact on material strength, fiber addition drew attention to the post-cracking behavior of the element. Results indicated that the higher the fiber content used, the greater was matrix`s residual strength, even after the element had already cracked, confirming the influence of fibers in reducing concrete’s brittleness. When evaluating shear strength, the addition of 0.5% and 1.5% of fibers resulted in a reduction of 19.89% and 23.41%, respectively. However, for the normalized resistances, there is no statistical difference between the values, in addition to the resistance reduction of 11%, for both fiber volumes. Predictive equations proved to be conservative for the reference mix and possibly applicable to fiber-reinforced mixes.